Effectiveness of Different Algorithms and Cut-off Value in Preeclampsia First Trimester Screening - Piotr Tousty; Bartosz Czuba; Dariusz Borowski; Magda Fraszczyk-Tousty; Sylwia Dzidek; Ewa Kwiatkowska; Aneta Cymbaluk-Płoska; Andrzej Torbé; Sebastian Kwiatkowski (Journal of Pregnancy)
Objectives and methods. The first aim of our study was to assess the detectability of women at risk of developing eo-PE depending on the algorithm used. All 801 patients had an estimated risk of eo-PE based on the Fetal Medicine Foundation algorithm. The patients were divided into four groups based on a risk calculation algorithm: 1) screening based on UtPI, MAP, and PlGF; 2) screening based on UtPI, MAP, PAPP-A, and PlGF; 3) screening based on UtPI, MAP, and PAPP-A; and 4) screening based on UtPI and MAP. The second aim was to explore how these groups changed depending on the cut-off points for the increased risk of eo-PE. We selected patients within groups where the risk of eo-PE was >1 : 150. Among them, the UtPI, MAP, PAPP-A, and PLGF values were compared taking into account the sizes of the groups. Results. For the cut-off point >1 : 150, 86 women at an increased risk of eo-PE using algorithm 1 were identified. Of these 86 patients, 83 (96%) were identified using algorithm 2, 62 (72%) using algorithm 3, and 60 (69%) using algorithm 4. In addition, it was demonstrated that between 21% and 29% of women at a low risk of eo-PE could be given acetylsalicylic acid if a screening test was used that did not account for PlGF. Conclusions. In order to provide the highest level of health care to pregnant women, it is extremely important that full screening for eo-PE should be ensured. The cheapest algorithm based only on MAP and UtPI resulted in our patients being unnecessarily exposed to complications.